PENGARUH KOMUNIKASI, KOMITMEN ORGANISASIONAL, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. NASMOCO MAJAPAHIT, SEMARANG - Luksia Eva Relawati, 15.05.51.0257; Kasmari, Kasmari (Students' Journal of Economic and Management, 2019)
This research was conducted at PT. Nasmoco Majapahit, Semarang, where the reason for choosing PT. Nasmoco Majapahit, Semarang as the object of research because of the decline in the achievement of Toyota car sales. This is certainly a problem whose solution must be sought with the aim of research is to analyze the influence of communication, commitment organizational and organizational culture on employee performance. The study population was 51 responses. The number of samples in this study is determined by means of stratifie random sampling which is classifying the population into sub-populations based on the type of work, then selected from each sub-population with a proportional method to obtain the number of elements in each sample unit. Data analysis method used with linear regression as a hypothesis testing. The results of the study found (1) partially (individually) there was a positive and significant influence between communication on employee performance; (2) partially (individually) there is a positive and significant influence between commitment organizational to employee performance; (3) partially (individuals) there is a positive and significant influence between organizational culture on employee performance.